Comparative analysis of Hermetia illucens L. mixed chicken feed and commercial chicken feed to growth performance, carcass weight, and meat proximate content of Gallus domesticus L. - Muhamad Aldi Nurdiansyah; Agus Dana Permana (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The development of the broiler farming industry to meet the needs of chicken meat in Indonesia has problems including the availability and high prices of commercial feed. This is due to the use of high-priced protein sources from a fish meal as a commercial feed composition. One option that can replace a fish meal as a composition of broiler feed is Hermetia illucens L. larvae flour. This study aims to determine the difference between H. illucens mixed chicken feed (HiMCF) and commercial chicken feed (CCF) on growth performance of Gallus domesticus L. with parameters Final Body Weight (FBW), Daily Feed Intake (DFI), Daily Weight Gain (DWG), Feed Conversion Ratio (FCR), Approximate Digestibility (AD), Efficiency of Conversion Digestibility (ECD), carcass weight with 3-joint wings, forequarter, and leg quarter, and the meat proximate content. In this study, G. domesticus were cultivated for 33 days with HiMCF and CCF treatment. The complete proximate content of feed and meat was analyzed descriptively, while growth and carcass weight were analyzed by statistical SPSS T-test (T-test, = 0.05). The feeding of HiMCF and CCF treatment on the growth of broiler chickens to DFI, DWG, FCR, AD, and ECD was the same except for FBW. While the feeding of HiMCF and CCF treatment to the carcass weight was not the same except for 3-joint wings. The feeding of HiMCF and CCF treatment gave the same proximate content of broiler chicken meat. Based on this research, the HiMCF can be an alternative feed for broiler chickens.